An Assessment of Zinc Fluxes by Analyzing Monthly, Weekday, and Weekend Levels in a River. Issue 6 (23rd March 2022) - Andarani, Pertiwi; Yokota, Kuriko; Inoue, Takanobu; Alimuddin, Hardianti; Nguyen, Minh Ngoc
Abstract: Unlike other potentially toxic metals, zinc (Zn) is indispensable to life but also poses environmental risks to aquatic organisms. Aichi Prefecture has the Japan's fourth‐highest discharges of Zn into water bodies. It is likely that the Zn fluxes in Aichi's water bodies originate from industrial wastewater. This study evaluates the spatial‐temporal and diel variability of Zn on sunny days during weekdays and weekends in the Umeda River. The most downstream point is considered as the most polluted section according to the monthly survey [dissolved Zn (D‐Zn): 0.0046–0.0719 mg L −1, particulate Zn (P‐Zn): 0.42–2.01 mg g −1 ] that varied between seasons (coefficient of variation: 95% for D‐Zn; 53% for P‐Zn). The total Zn (T‐Zn) concentrations on weekdays (0.015–0.043 mg L −1 ) at the most downstream point exhibit much higher concentrations than those during the weekends (undetected–0.032 mg L −1 ). Given the dissolved phase of these Zn levels (77 ± 11%), the Zn are likely discharged by industrial facilities on weekdays. The T‐Zn loading on weekdays (56 g km −2 d −1 ) is approximately three times higher than that on weekends. At least 67% of the T‐Zn and 70% of the D‐Zn fluxes from industrial point sources are potentially discharged on weekdays. Abstract : Although zinc (Zn) is essential to life, it poses a toxic effect to aquatic organisms; hence, several countries enacted a stringent regulation for Zn, including Japan. A monthly survey revealed that winter shows the highest Zn concentration. On weekdays, the industrial point sources may have contributed ≈67% of total Zn and 70% of dissolved Zn concentrations, while the particulate Zn is likely adsorbed by particulate organic carbon and particulate Fe.